Interdisciplinární výzkum archeologických artefaktů pomocí moderních technologií - Ladislav Čapek; Lukáš Holata; Petr Menšík; Petr Baterl; Jan Hrdlička; Jan Říha; Jarmila Savková; Pavel Vařeka (AntropoWebzin, 2014)
The paper introduces results of projectof interdisciplinary research of artifacts throughmodern technologies based on archaeometricstudy of Prehistoric and Middle Age pottery andon chemical analyses of soils around a desertedmedieval village. Processes of production and useof the ceramic artifacts in the past society may bestudied in a better way through modern archaeometricmethods; chemical analyses of soils enablea non-destructive understanding of inner structureof areas of activities and components on archaeologicalsites. Chemical analyses of soils onthe basis of phosphate analysis were applied onexample of the deserted medieval village called Sloupek (Rokycany region) where it was possibleto defi ne spatial structure of activities in terms ofone farmstead on the basis of phosphate distributionand we were able to interpret processesrelated to abandonment of the site followed byorganic remains. Archaeometric analyses of thesettlement pottery from the Younger Bronze Ageand Middle Age pottery from České Budějovice enabled us to understand the structure of the ceramicraw material and character of the potteryproduction. It is possible to take into considerationlocal or regional production of Middle Ageas well as Prehistoric pottery on the basis of theidentifi ed characteristics which was not related toany other production spheres.